Design of Multi-core Processor Software with Pipelining Strategy - Jian Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
At present, in the field of application of numerous IT, multi-core processors are widely used, the hardware development is much faster than the speed of software development. Multi-core processor software is using the design concept of single-core processor software, so this software is not high-performance and the performance processor is not fully played. This paper firstly introduces the traditional software design method based on multiple cores, and then points out two problems existing in it.To improve its efficiency, I propose a method called pipeline which can improve processor utilization and the throughput of a processor, at the same time, reduce the cost of the system. This method has been verified in the network packet processing. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4811